2010
DOI: 10.1152/ajpheart.01096.2009
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal relationship between adiponectin and LOX-1 in the regulation of endothelial dysfunction in ApoE knockout mice

Abstract: We hypothesized that the reciprocal association between adiponectin and lectin-like oxidized LDL (ox-LDL) receptor (LOX)-1 contributes to the regulation of aortic endothelial dysfunction in atherosclerosis. To test this hypothesis, endothelium-dependent (ACh) and endothelium-independent (sodium nitroprusside) vasorelaxation of isolated aortic rings from control mice, apolipoprotein E (ApoE) knockout (KO) mice, and ApoE KO mice treated with either adiponectin (15 microg x day(-1) x mouse(-1) sc for 8 days) or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
4
35
1
2
Order By: Relevance
“…A major vasodilator substance released by the endothelium is NO (9,11,12). Reduced NO bioavailability by both decreased production and inactivation of NO is associated with the initiation, progression, and complications of atherosclerosis (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A major vasodilator substance released by the endothelium is NO (9,11,12). Reduced NO bioavailability by both decreased production and inactivation of NO is associated with the initiation, progression, and complications of atherosclerosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…A major vasodilator substance released by the endothelium is NO (9,11,12). Reduced NO bioavailability by both decreased production and inactivation of NO is associated with the initiation, progression, and complications of atherosclerosis (9). Because endothelial dysfunction is considered to be an early stage of atherosclerosis, understanding the mechanisms involved is a major goal for devising therapeutic treatments for atherosclerosis (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the formation of foam cells is predominantly regulated by these SRs and reverse cholesterol transporters (RCTs). Recently, a growing body of evidences has shown that some kinds of adipokine, such as adiponectin, leptin, and vaspin, may affect cholesterol accumulation in macrophages and, thus, accelerate or retard the process of atherosclerosis through modulation of SRs or RCTs (Chen et al 2010;Spiroglou et al 2010;Kopff and Jegier 2005;Kjerrulf et al 2006).…”
Section: Introductionmentioning
confidence: 99%